AN ANALYSIS OF SOCIAL AND CULTURAL ISSUES REFLECTED IN KID’S TALK, AN EFL TEXTBOOK FOR ELEMENTARY SCHOOL - Diah Suharyati (Journal of English Education Program (JEEP), 2015)
This paper aims at investigating social identity and the dominant gender through images in the textbook. This research was analyzed by classifying gender based on social identity theory (Byram et al, 1994), and analyzed occupational stereotyping (Sunderland, 1994a, pp. 55-56).The population of this study was 896 images in the textbook and 46 images based on occupation chosen purposively as the sample. The writer used semiotic approach as tool to support this study especially Saussures’ categories. The findings occupations of male and female was found similarity of percentages, especially in dancer, painter, secretary, nurse, architect and nanny in male were not found, whilst in female, baker, seller, barber, driver, porter, waiter, racer, office worker and doctor also not found. The dominant gender in the textbook was male based on occupations. It proved with the number of male more than female. From the results above, the writer conclude that the result of this study obtained gender bias. It was proved with male tend to occupy more great occupations than female.Keywords: social identity, culture, gender, semiotics and textbook.